Room a novel - Donoghue, Emma 1969- (Picador, 2011)
It's Jack's birthday and he's excited about turning five. Jack lives with his Ma in Room, which has a locked door and a skylight, and measures 11 feet by 11 feet. He loves watching TV but he knows that nothing he sees on screen is truly real. Until the day Ma admits that there's a world outside
Originally published: 2010
Keywords: Mother and child / Fiction; Boys / Fiction; Fiktionale Darstellung